Terbentuknya White Layer pada Proses Milling Austempered Ductile Iron (ADI) - Rusnaldy, Rusnaldy; Umardani, Yusuf (ROTASI, 2020)
Machining processes cause a white layer at the surface of a work piece. A white layer is a featureless layer that typically forms on machined steel surfaces and appears white when observed under an optical microscope after standard metallographic preparation. A white layer is known to be a function of the cutting conditions and its thickness ranges from a few microns to a few tens of microns. A white layer is generally a hard phase and leads to the surface becoming brittle causing crack permeation and product failure. This layer has been reported in a wide range of materials, from mild steels to nickel-based super alloys. This paper reports on an investigation of white layer formation for a range of cutting speeds, feeds and depth of cut  in milling of Austempered Ductile Iron (ADI). To produce ADI, ductile irons  were first austenitized in furnace at 900oC for 1 hour and then they were quenched in salt bath at 375oC for 1 hour.  The machined specimens were analysed using a optical microscope with software Lumenera Infinity 1 to measure the thickness of white layer dan a micro hardness tester. The present results reveal that white layers were formed on the machined surfaces of ADI. The machined surface showed an increase in hardness with respect to the bulk material. The effects of cutting speeds, feeds and depth of cut on thickness and micro hardness of  white layers are reported in this paper.